Kebijakan Moneter : Menjaga Keseimbangan Antara Inflasi, Jumlah Uang Beredar, dan Pertumbuhan Ekonomi - Icha Lesmana; Irna Della br Ginting; Legi Likasri Simbolon; Nataline Simanjuntak (Trending: Jurnal Manajemen dan Ekonomi, 2025)
Monetary policy is a key instrument in maintaining a country's economic stability. An imbalance between the money supply and inflation can negatively impact economic growth, purchasing power, and price stability. This study analyzes the role of monetary policy in controlling inflation and money supply to promote stable and sustainable economic growth. The study employs a qualitative approach by analyzing secondary data from central bank reports, previous research, and relevant macroeconomic data. The findings indicate that monetary policy instruments, such as interest rates, open market operations, and reserve requirements, are effective in curbing inflation while maintaining economic growth. However, the effectiveness of these policies depends on global economic conditions and the real sector's response to monetary policy changes. Therefore, a flexible and data-driven policy is required to adapt to economic dynamics. These findings provide implications for policymakers in designing more adaptive monetary strategies to achieve long-term economic stability.